Transforming practice through culture change: probation staff perspectives on juvenile justice reform - Esthappan, Sino (Youth violence and juvenile justice, 2020)
Probation plays a central role in the juvenile justice system, and probation officers are often involved in numerous decisions made in juvenile courts. This study examines the views of probation staff from 23 jurisdictions, some of which participated in an Annie E. Casey Foundation–funded juvenile justice reform effort intended to safely and significantly reduce the use of out-of-home placements, especially for youth of color. We survey juvenile probation staff members at two waves and describe changes in reported practices and principles relating to individualized case planning, youth engagement, family and community engagement, and racial and ethnic equity and inclusion as well as beliefs about the purposes of out-of-home placement. Reform sites reported slightly more frequent use of practices and principles addressing community engagement and racial and ethnic equity and inclusion in the second wave than in the first wave.